2017
DOI: 10.1103/physrevc.96.054609
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneity growth in two-component fermionic systems

Abstract: The dynamics of fermionic many-body systems is investigated in the framework of BoltzmannLangevin (BL) stochastic one-body approaches. Within the recently introduced BLOB model, we examine the interplay between mean-field effects and two-body correlations, of stochastic nature, for nuclear matter at moderate temperature and in several density conditions, corresponding to stable or mechanically unstable situations. Numerical results are compared to analytic expectations for the fluctuation amplitude of isoscala… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 97 publications
1
38
0
Order By: Relevance
“…11, in comparison with the study of Ref. [23]), we concluded that for both semi-central and semi-peripheral impact parameters the leading wavelength related to the surface instability is roughly twice larger (λ = 20 f m) and the leading growth time can be up to ten times longer (t rupture = /Γ k ≈ 200 to 300 fm/c). As a consequence, rather massive fragments (roughly up to Germanium) are produced in such process with a formation time which, calculated from the onset of instabilities, extends over roughly 500 fm/c.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…11, in comparison with the study of Ref. [23]), we concluded that for both semi-central and semi-peripheral impact parameters the leading wavelength related to the surface instability is roughly twice larger (λ = 20 f m) and the leading growth time can be up to ten times longer (t rupture = /Γ k ≈ 200 to 300 fm/c). As a consequence, rather massive fragments (roughly up to Germanium) are produced in such process with a formation time which, calculated from the onset of instabilities, extends over roughly 500 fm/c.…”
Section: Discussionsupporting
confidence: 65%
“…In this work, in the same spirit of Ref. [40], where the 197 Au+ 197 Au system was also simulated, we employed a stochastic one-body approach which, in this new attempt, adopts a full treatment of the Boltzmann-Langevin equation in three dimensions, condensed in the BLOB model [23,42]. Such approach handles shape fluctuations in the dynamical evolution more consistently, while keeping an efficient description of collective behaviour relying on the mean-field formalism.…”
Section: Introductionmentioning
confidence: 99%
“…The latter was conceived with the purpose of including fluctuations in full phase space, thus improving the treatment of fluctuations and correlations, but preserving, at the same time, mean-field features such as the proper description of spinodal instabilities at low density [116]. The improvement introduced by the BLOB approach is primarily providing a correct sampling of the fluctuation amplitude in full phase space, yielding a faster fragmentation dynamics and also a consistent description of the threshold toward multifragmentation.…”
Section: Multifragment Emissionmentioning
confidence: 99%
“…As an illustrative example, Fig.13 shows the action of the isovector terms on the system 136 Xe+ 124 Sn (at 32 MeV/A), looking at fragment isotopic features. Results obtained with BLOB, employing an asystiff EOS, are displayed [116].…”
Section: Isotopic Featuresmentioning
confidence: 99%
See 1 more Smart Citation